Genotypic determination of resistance and heteroresistance to clarithromycin in Helicobacter pylori isolates from antrum and corpus of Colombian symptomatic patients (2017)
The effectiveness of Helicobacter pylori first line treatment has decreased drastically with the raise of strains resistant to clarithromycin. Therapy failure have also been described in patients with infections by strains with dissimilar antimicrobial susceptibilities. The present study aimed to estimate the prevalence of resistance and heteroresistance to clarithromycin in H. pylori isolates from antrum and corpus of Colombian patients.